2017
DOI: 10.1080/17571472.2017.1302872
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus and type 2 diabetes

Abstract: The prevalence of diabetes is higher amongst individuals infected with HIV. The major contributor to hyperglycaemia is thought to be iatrogenic, with protease inhibitors being most commonly associated to insulin resistance. This article is to update general practitioners on the diagnosis and management of diabetes in HIV-infected patients. Specific considerations are highlighted including interactions of particular diabetic drugs with antiretroviral therapy (ART). We articulate why the use of Hemoglobin A1c (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…In terms of glycemic control, PWH undergoing CC had significantly higher HbA1c levels compared to those that did not have a CC. No differences were noted in the diagnoses of type I or II DM, although abnormal glycemic control and metabolic syndrome among these patients may certainly increase the risk of CVD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of glycemic control, PWH undergoing CC had significantly higher HbA1c levels compared to those that did not have a CC. No differences were noted in the diagnoses of type I or II DM, although abnormal glycemic control and metabolic syndrome among these patients may certainly increase the risk of CVD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As also highlighted in the literature, our results TDF confirmed that TDF has not any significant effect on glucose metabolism. Moreover, PIs (especially indinavir and ritonavir) were associated with hyperglycemia, potentially mediated by Glut4 glucose transporter inhibition . Several case studies reported hyperglycemia in patients who started InSTI‐based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67] HIV patients treated with immunosuppressive agents may have HbA1c discordant with blood glucose levels which therefore results in an underestimation in the prevalence of dysglycemia; 68 the HbA1c, therefore, should not be used to assess glycemia in this population. 69 To summarize, although HbA1c is a valuable tool for the diagnosis of dysglycemia, screening for high-risk individuals using the HbA1c alone may not be sufficient to substitute for the information derived from OGTT.…”
Section: Hba1cmentioning
confidence: 99%
“… 65 67 HIV patients treated with immunosuppressive agents may have HbA1c discordant with blood glucose levels which therefore results in an underestimation in the prevalence of dysglycemia; 68 the HbA1c, therefore, should not be used to assess glycemia in this population. 69 …”
Section: Hba1c Not Reliable For Detecting Early Dysglycemiamentioning
confidence: 99%